Suture Versus Screw Fixation of Tibial Spine Fractures in Children and Adolescents: A Comparative Study. Issue 11 (22nd November 2019) - Callanan, Mark; Allen, Judd; Flutie, Brett; Tepolt, Francis; Miller, Patricia E.; Kramer, Dennis; Kocher, Mininder S.
Background: Tibial spine fractures involve an avulsion injury of the anterior cruciate ligament (ACL) at the intercondylar eminence, typically in children and adolescents. Displaced fractures are commonly treated with either suture or screw fixation. Purpose: To investigate differences in various outcomes between patients treated with arthroscopic suture versus screw fixation for tibial spine avulsion fractures in one of the largest patient cohorts in the literature. Study Design: Cohort study; Level of evidence, 3. Methods: A search of medical records was performed with the goal of identifying all type 2 and type 3 tibial spine avulsion fractures surgically treated between 2000 and 2014 at a pediatric hospital. All patients had a minimum of 12 months clinical follow-up, suture or screw fixation only, and no major concomitant injury. Results: There were 68 knees in 67 patients meeting criteria for analysis. There were no differences with regard to postsurgical arthrofibrosis ( P = .59), ACL reconstruction ( P = .44), meniscal procedures ( P = .85), instability ( P = .49), range of motion ( P = .51), return to sport ( P >.999), or time to return to sport ( P = .11). Elevation of the repaired fragment on postoperative imaging was significantly greater in the suture group (5.4 vs 3.5 mm; P = .005). Postoperative fragment elevation did not influence surgical outcomes. The screw fixation group had more reoperations (13 vs 23; P = .03), a larger number of reoperations for implant removal (3 vs 22; P < .001), and nearly 3 times the odds of undergoing reoperation compared with suture patients (odds ratio, 2.9; P = .03). Conclusion: Clinical outcomes between suture and screw fixation were largely equivalent in our patients. Postoperative fragment elevation does not influence surgical outcomes. Consideration should be given for the greater likelihood of needing a second operation, planned or unplanned, after screw fixation.